Is Love All You Need? The Effects of Emotional Culture, Suppression, and Work–family Conflict on Firefighter Risk-Taking and Health - O’Neill, Olivia Amanda; Rothbard, Nancy P. (Academy of Management Journal, 2017)
In this paper, we build and test theory about the emotional cultures of prototypically masculine organizations. A qualitative study of fire stations in a major metropolitan area revealed that the emotional cultures of firefighting units were defined by two emotions: joviality and companionate love. In addition, emotion suppression, work–family conflict, risk-taking, and health problems emerged as central themes. A multirater survey study of firefighters across multiple units found that cultures characterized by both high joviality and high companionate love were associated with decreased risk-taking behavior outside of work. Additionally, emotion suppressors who experienced high work–family conflict reported more risk-taking behavior outside of work. Suppressors who experienced higher work–family conflict reported more health problems in strong cultures of joviality, but fewer health problems in strong cultures of companionate love. Longitudinal exploratory analyses of objective performance indicators revealed that, although units characterized by strong joviality had better response times, they were also more likely to have auto accidents and property loss than units weak in joviality, with some evidence that companionate love might attenuate risky behavior on the job. Our findings contribute to a more nuanced understanding of gender, emotions, and organizational culture.